Reversible and irreversible fluorescence activity of the Enhanced Green Fluorescent Protein in pH: Insights for the development of pH-biosensors - dos Santos, Nathalia Vieira [UNESP] (2020)
Enhanced Green Fluorescent Protein (EGFP) is a biomolecule with intense and natural fluorescence, with biological and medical applications. Although widely used as a biomarker in research, its application as a biosensor is limited by the lack of in-depth knowledge regarding its structure and behavior in adverse conditions. This study is focused on addressing this need by evaluating EGFP activity and structure at different pH using three-dimensional fluorescence, circular dichroism and small-angle X-ray scattering. The focus was on the reversibility of the process to gain insights for the development of biocompatible pH-biosensors. EGFP was highly stable at alkaline pH and quenched from neutral-to-acidic pH. Above pH 6.0, the fluorescence loss was almost completely reversible on return to neutral pH, but only partially reversible from pH 5.0 to 2.0. This work updates the knowledge regarding EGFP behavior in pH by accounting for the recent data on its structure. Hence, it is evident that EGFP presents the required properties for use as natural, biocompatible and environmentally friendly neutral to acidic pH-biosensors.